Stand like a cedar - Campbell, Nicola I. (Highwater Press, 2020)
"Children go for a walk in the woods with their elders and discover the animals of British Columbia, their names in the Nłe7kepmxcín or Halq'emeylem languages, and the teachings they have for us."--